Erratum to "Detection of rarely identified multiple mutations in MECP2 gene do not contribute to enhanced severity in Rett syndrome", Am J Med Genet Part A 161A:1638–1646. Issue 5 (May 2014) - Chapleau, Christopher A.; Lane, Jane; Kirwin, Susan; Schanen, Carolyn; Vinette, Kathy M. B.; Stubbolo, Danielle; MacLeod, Patrick; Glaze, Daniel G.; Motil, Kathleen J.; Neul, Jeffrey L.; Skinner, Steven A.; Kaufmann, Walter E.; et al.
<x xml:space="preserve">Abstract</x> © 2014 Wiley Periodicals, Inc.